Mastitis in Dairy Cattle, Sheep and Goats - Kerro Dego, Oudessa (IntechOpen, 2022)
Mastitis, an inflammation of the mammary glands, is the most costly disease in dairy farming, mainly caused by a broad range of bacteria categorized into contagious and environmental bacteria. This book is a concise summary of mastitis in dairy cattle, sheep, and goats, which mainly focuses on etiological agents, epidemiology, pathogenesis, clinical manifestation, pathological and histopathological changes, diagnosis, prevention, and control measures. This book serves as a textbook on mastitis in dairy cattle, sheep, and goats for dairy veterinarians, veterinary students, animal science students, dairy technicians, animal health professionals. Several researchers worldwide contributed to this book. This book contains the latest information on mastitis in dairy cattle, sheep, and goats and antimicrobial usage to prevent and control mastitis.